Effectiveness Socialization Program of The Micro Small and Medium Enterprises - Hariyo Hariyo; Hulwati Hulwati; Aidil Novia; Afrinal Afrinal (Journal of Islamic Economics and Finance Studies, 2025)
This study aims to analyze the socialization of the Bayang Bungo Indah SMEs program and its impact on business participation. This research uses a qualitative method with a case study approach (case study design). Data sources were taken from sixty-six informants through in-depth interviews selected using purposive sampling technique, all informants were active business actors totaling 66 people. All interview results were then analyzed using simple mathematical and statistical methods. The results of the analysis found that socialization has been maximized because the Chairperson is actively socializing the Bayang Bungo Indah SMEs program and the socialization is well delivered and very easily accepted by members. The Chairperson also said that this program is very helpful for community welfare because business actors can easily manage their businesses. Socialization is needed by SMEs members because this will affect the implementation of the SMEs program itself, the role of the chairman and assistants is quite large in the implementation of the Bayang Bungo Indah SMEs program, because the chairman and assistants are expected to solve the problems faced by each group.